Identifying the Internal and External Pressures of Quantifying the Impacts of Sustainability-Oriented Innovation - Al Owais, Abdelaziz Abdalla (International Review of Management and Marketing, 2024)
The sustainability-oriented innovation (SOI) has emerged as a critical approach for an organisation that addresses environmental, social, and economic challenges. The proposed study aims to identify key internal and external pressures by uncovering the main factors within and outside the organisation influencing the quantification of SOI impacts. In the given study’s research design adopts a primary qualitative approach to explore internal and external pressures affecting the quantification of sustainability-oriented innovation (SOI) that impacts the economic context. Qualitative research was chosen for its ability to provide an in-depth insight into a complex phenomenon that captures the nuances of the participant’s experience, attitudes and perception. The findings show that a leadership team’s commitment to sustainability and the proactive mindset of our employees fosters an environment where innovation thrives. The conclusion is that the implementation of internal policies and incentives encouraged sustainable practices and continuous improvement. SOI has been influenced by concepts like a crucial economy that promotes a continuation use of resources through its recycling and remanufacturing and to share economy, emphasizing access to over ownership.